ANALISIS EFISIENSI KEBIJAKAN PEMBERIAN KREDIT NON PERFORMING LOAN (NPL), BEBAN OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP PROFITABILITAS PADA PT BANK MANDIRI (PERSERO) Tbk PERIODE TAHUN 2014-2024 - Pratiwi Damayanti; Achmad Ludvy (Journal of Research and Publication Innovation, 2025)
This study aims to analyze the effect of credit policy efficiency, represented by Non-Performing Loans (NPL) and Operating Expenses to Operating Income (BOPO), on the profitability of PT Bank Mandiri (Persero) Tbk during the period of 2014–2024. A quantitative approach with descriptive methods and regression analysis is employed to examine the relationship and influence among the variables. The data used is secondary data. The analytical methods employed include descriptive statistical analysis, Pearson correlation test, Z-test, Wald Chi-Square test, and Stochastic Frontier Analysis (SFA) as well as efficiency analysis. The results indicate that both NPL and BOPO have a significant effect on Operating Profit Margin (OPM), either partially or simultaneously. Higher NPL and BOPO ratios reflect lower efficiency in credit and operational management, which negatively impacts profitability. Conversely, improved efficiency in managing credit and operational costs contributes positively to operating profit growth.